(untitled) (Bangladesh Journal of Neurosurgery, 2021)
Background: Medulloblastoma is a common malignancy in the paediatric population, accounting for 25% of all childhood brain tumors. The increasing magnitude of childhood cancer has become a threatening problem in developing countries like Bangladesh. But we have not enough data regarding the diseases of the children of Bangladesh. There is no literature available to shed light on Clinico-pathological types, diagnostic facilities and treatment patterns of this childhood cancer in our population. So this study is an opportunity to have experience about pediatric medulloblastoma of Bangladesh. Methods: The study conducted from January 2014 to December 2018 at National Institute of Cancer Research and Hospital (NICRH). Data are collected from admitted children aged under 18 years in the department of Pa ediatric Hematology and Oncology (PHO) and confirmed by histopathology and/or immunohistochemistry after collection of tissues from pathological lab. The data were obtained from statistical analysis by PSPP software Results: During 2014 to 2018 total diagnosed cases of childhood meduloblastoma were 57 but data were analyzed from only 52 patients. Male female ratio was 1.9:1. Median age of our patients was 6.12 years. Most common clinical features at preoperative assessment were vomiting, headache, fever, convulsion, eye/vision involvement. Hydrocephalus was Present in 48 (92%) cases. Radiologically distal metastasis were found in 2 (3.85%) cases. Tumor resection was performed in all patients and total removal in 56.80% (N-25), gross total removal 25% (N-11), and partial removal 18.20% (N-8) and in 8 cases resection type were not elicited. Pathological grading were recorded in 52 patients , where all were Grade-IV (100 %).Within 22 months of follow up time absconded patients were 44.4%, partially treated cases are 9.6% with high death rate (23%). Regular treated cases with good outcome were 23%. Conclusions: Medulloblastoma is a challenging condition for neurosurgeon, radiotherapist and oncologists of Bangladesh. We have to reduce the abandon cases; review the risk stratification by using molecular profile and enhance the support service to improve the survival rate. RT- radiotherapy, CT-Chemotherapy, UB-Urinary Bladder. All patients underwent preoperative Computed tomography (CT) or Magnetic resonance imaging (MRI) of head (Fig.1) But 90.4% (N-47) MRI/CT reports were able to given a proposed diagnosis like medulloblastoma or ependymoma, 5.7% (N-3) diagnosed as space occupying lesion (SOL) and 2 (3.9%) case didn’t make any remarks regarding the brain lesion (Table-3).Tumors arise from midline (Vermis) were 71.15% (N-37 ) and from hemisphere were 28.85% (N-15). Bang. J Neurosurgery 2021; 10(2): 154-162